# 9.2 – Adding & Subtracting Rational Expressions. Remember adding & subtracting fractions?

## Presentation on theme: "9.2 – Adding & Subtracting Rational Expressions. Remember adding & subtracting fractions?"— Presentation transcript:

9.2 – Adding & Subtracting Rational Expressions

9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator!

9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4

9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 4 3

9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 4 3

9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 4 3 4 3 12

9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 _ 9 4 3 4 3 12 12

9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 _ 9 = 4 3 4 3 12 12

9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 _ 9 = _ 1 4 3 4 3 12 12 12

9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 _ 9 = _ 1 4 3 4 3 12 12 12 –Same w/rational expressions!

Ex. 1 Simplify each expression

a. 6 + 8 ab a

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + ab a ab

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a(b)

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a(b) = 6 + 8b ab ab

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a(b) = 6 + 8b ab ab = 6 + 8b ab

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a(b) = 6 + 8b ab ab = 6 + 8b ab

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m (m+2)(m-2)

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2)

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2)

Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m 3(m+2)(m-2)

Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2)

Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2)

Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2)

Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2)

Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4

Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4 3(m+2)(m–2)

Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4 = m + 4 3(m+2)(m–2)

Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4 = m + 4 _ 3(m+2)(m–2)